Ethnomedicine Study of Medicinal Plants for Therapy of Elderly Sleep Disorders in Tengger Tribe - Lahardo, Devanus; Ekasari, Wiwied; Widyawaruyanti, Aty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Ethnomedicine offers valuable insights into plant-based therapies, potentially leading to the discovery of novel drugs. Sleep disturbances, including difficulty falling asleep, maintaining sleep, and early morning awakening, are prevalent among the elderly population and can significantly worsen Alzheimer's disease progression. This study explores the medicinal plants utilized by the Tengger tribe's elderly population for treating sleep disorders. Employing a mixed-methods approach, the study involved qualitative data collection through snowball sampling and in-depth interviews with 99 elderly participants and three traditional healers of the Tengger tribe. Quantitative data was obtained through questionnaires administered during field surveys. Participants were selected based on specific criteria: elderly individuals over 60 years of age, native Tengger tribe members with a history of using medicinal plants for sleep disorders; traditional healers were required to be native Tengger tribe members with knowledge passed down through generations. The study identified a total of 11 medicinal plants used for sleep disorders. Five plant species emerged as the most dominant based on the highest citation value (FC) analysis: kale (Ipomoea reptans), agarwood (Aquilaria malaccensis), sintok (Cinnamomum sintoc), Broadleaf plantain (Plantago major), and soursop (Annona muricata). The most commonly used plant parts were leaves, bark, and roots. Traditional preparation methods included boiling and burning the plant materials. Notably, knowledge of these medicinal plants is primarily transmitted orally within the community. Our findings highlight five medicinal plants employed by the Tengger elderly to manage sleep disorders, with limited documented evidence of their efficacy.